Ecoenzyme Making Training for the Community in Cipanas Village as a Waste Management Innovation - Leny Heliawati; Prasetyorini Prasetyorini; Surti Kurniasih; Rita Retnowati; Putri Nabila Adinda Adriansyah (Yayasan Keluarga Guru Mandiri, 2025)
Cipanas Village is classified as densely populated without landfills or institutions in charge of processing waste. This village accumulates mostly household organic waste in the form of vegetables, fruit, or other organic waste. To overcome the waste problem in this village, the community service team conducted socialization and demonstrations in making ecoenzymes to overcome organic waste problems. The ecoenzyme solution has many benefits, such as a cleaning solution, plant fertilizer, and many more. This community service activity consists of two stages: socialization and demonstration. This community service activity was very well received by the Cipanas Village community, as seen by the enthusiasm and many questions asked by the participants about the socialization and demonstration of making ecoenzymes. Community service activities like this are hoped to be carried out sustainably, encouraging people to be creative and innovative in creating a clean and waste-free environment while making products of ecoenzymes that are very beneficial for people's lives.